Ruling the Underground: Governance and Agency in a basement in Hillbrow - Rubin, Margot; Gewer, Hayley; Campbell, Morag; van den Bussche, Jennifer (South African Research Chair in Spatial Analysis and City Planning, 2016)
An unexpected answer a chance encounter, led to the discovery of the life and everyday experiences of people living and working in a basement in Hillbrow, Johannesburg. Unseen from the street level and only known to “insiders” who work and live in the inner city, the basement is used every hour of every day. It is home, work and leisure space, where the sacred and the profane sit side by side. Children are cared for, objects are assembled, taken apart or taken away, deals are made and prayers are offered; all to the steady rhythms of hammering, welding, singing and drumming that signal the hours, days, weeks and months that pass by. This report outlines the informal governance relations and socially determined rules that allow for the creation of multiple purposes in a space that has been reterritorialised and repurposed. It also attempts to tell the story of life in a basement, considering its cycles, rhythms and beats within a space that simultaneously typifies the lived experience and working lives of many low-in- come people in Hillbrow. The basement affords important and invaluable opportunities for trying to understand a range of social and economic experiences and practices that take place within spaces that are informally regulated and hid- den. Thus far, much existing research has focused predominantly on everyday social and economic engagements and interactions that occur at street level, or in demarcated spaces such as markets. In these spaces performativity and agency are more visible and, as such, are better able to be scrutinised and controlled. By contrast, activities within the basements are hidden, and occur within spaces where the distinctions between formal and informal, regulated and unregulated, legal and illegal are even more blurred and difficult to understand than those observed above the ground. This report presents an argument that invisibility, being beyond the gaze of the state, is an invaluable asset for many poorer people. Such “invisibility” ensures that the basement dwellers and users can live and work outside of the rules, regulations and laws that would otherwise deny them income or shelter. However, it goes further and demonstrates that the invisible and the informal do not equate with the chaotic or anarchic, as is the case so often presented. It explains how the often complex, yet still enduring and supportive nature of the socially determined rules of operations and relationships, occur within such a space. The report also speaks to the idea of reterritorialisation, yet moves beyond an acknowledgement that such a process does take place, to an investigation into exactly how spaces are repurposed and retrofitted for new uses. We assert that reterritorialisation is as much about the physical adaptation of the space and reconstructing its materialities, as it is about re-working the rules that govern its use. Thus there is an interlocking process whereby physical change is reinforced through new rules for the territory which, in turn, allow and support both the physical transformation as well as the new uses of space. One without the other would be impossible. As such, this research begins analysing the complex dynamics that arise at the intersection of space, scale, networks and agency, in a particular setting. Current planning procedures and policies do not account for the broad (and expanding) spectrum of diverse urban practices currently occurring within the inner city. A city’s response to these urban challenges is often to try and eliminate such practices through rules and discourses of perceived normalisation. Given the necessity and embeddedness of the spaces under review in this research, it would seem more productive to rethink and redefine policies and regulations in ways that would enable people to work and live more functionally, and with integrity. The report begins with a reflection on our process and experiences of conducting research in the precarious spaces of inner city basements in Hillbrow, and the difficulties and challenges that arise when “outsiders” enter these spaces. We ask questions around what this means for the research, the findings, the researchers themselves and, most importantly, the respondents. Following this meditation, we discuss our theoretical framing, which moves away from the traditional discussion of formality and informality. Rather, our choice is to present the findings from our work through an adaptation of Lefebvre’s (1994) notions of rhythms and cycles as the structuring elements of the discussion, and to demonstrate how the activities in the basement have rhythms and cycles that differ in lengths and intensities. Embedded within these rhythms and cycles, questions emerge that relate to how space has been repurposed, how livelihoods are sustained, and how daily management and governance facilitates these temporal phases and processes. The final section provides key conclusions, and offers some ideas on how to support these spaces without interfering and destroying what is taking place.
Keywords: urban; Hillbrow; basement; governance; agency